INVESTIGATION OF DIFFERENT EXPOSURE SETTINGS FOR IMAGE QUALITY AND ENTRANCE SKIN DOSE - Abdul Majid, Zafri Azran (International Journal of Allied Health Sciences, 2018)
Introduction: The ideal imaging system that is providing a good quality image of minimal radiation dose. There are many parameters that influenced image quality and radiation dose on clinical radiography. This study has identified some of the problems whereby there are practitioners do not select the proper size of image receptor (IR) and collimation during the examination. The re-usable of the IR and imaging plate also need to be concerned whether multiple exposures may affect the image quality or not. The purpose of this study is to investigate the effect of different exposure settings; kVp, mAs, collimation field sizes and different IR’ sizes for image quality and radiation dose. Methods: The wall-mounted x-ray machine act as a sources of radiation which exposed the acrylic cylinder that placed over the IR. The examination is repeated with different kVp, mAs, collimation field sizes and IR’s sizes. The source to image distance (SID) is fixed to 100 cm distance and put Nano dot dosimeter similar level with the top of acrylic to measure the dose. The result analysed by using software ImageJ to measure the Contrast to Noise Ratio (CNR). Results: The percentage of CNR1 and CNR2 reduced as the kVp is increased from (CNR1=77.25, CNR2=64.45), (CNR1=73.47, CNR2=61.22) and (CNR1=62.80, CNR2=57.32) for 50 kVp, 75 kVp and 100 kVp respectively and fluctuate when mAs increased. The CNR and entrance skin dose (ESD) shows higher when x-ray beam collimate according to IR’s size. Conclusions: Overall, the manipulative effect of exposure settings on image quality and ESD shows some positive results. The result also shows inconsistent readings in the CNR and ESD. The percentage of CNR decreased when kVp increases and slightly fluctuate when mAs increased. The ESD reading depicts higher when the kVp and mAs increase as well as when x-ray beam collimated according to IR’s sizes.